MENIMBANG METODE JOHN WANSBROUGH DAN FAZLUR RAHMAN DALAM STUDI AL-QURAN - Machrus, Machrus (Jurnal THEOLOGIA, 2013)
Abstract: One of aspects of Islam studied by orientalists is the Qurâ€™an. They have written many books on the Qurâ€™Än. One of themes of Qurâ€™anic studies written by orientalists are about influences of Judeo-Christianity tradition in the Qurâ€™Än. They try to prove the influences of Judeo-Christianity tradition in the Qurâ€™Än. One of orientalists who try to prove the influences of Judeo-Christianity tradition in the Qurâ€™Än is John Wansbrough, a Jewish orientalist. In studying the Qurâ€™Än, Wansbrough uses literary analysis, an analysis based on the text apart from historical context. He does not believe in historical context relates to Qurâ€™anic revelation. Whereas Qurâ€™anic revelation relates to the events occurred in Muá¸¥ammadâ€™s life time. By using historical approach, Fazlur Rahman proves that qurâ€™anic revelation relates to the history so-called asbÄb al-nuzÅ«l. Rahman insists that the study of the Qurâ€™Än done by Wansbrough does not make sense. Abstrak: Di antara aspek-aspek dalam Islam yang dikaji oleh para orientalis adalah al-Quran. Sudah banyak karya mengenai al-Quran yang dihasilkan oleh para orientalis. Sebagian dari karya orientalis mengenai al-Quran bertemaÂ¬kan pengaruh Yahudi-Kristen dalam al-Quran. Para orientalis mencoba untuk membuktikan adanya pengaruh Yahudi-Kristen. Salah satu dari mereka adalah John Wansbrough. Ia mengkaji al-Quran dengan menggunakan analisis sastera (literary analysis), suatu analisis yang didasarkan pada teks terlepas dari konteks sejarah. Ia tidak mempercayai bukti-bukti sejarah berkaitan dengan turunnya al-Quran. Padahal turunnya al-Quran berkaitan dengan peristiwa-peristiwa yang terjadi masa Nabi Muá¸¥ammad. Hal ini dibuktikan dengan analisis sejarah yang dilakukan oleh Fazlur Rahman. Rahman sendiri dengan tegas mengatakan bahwa kajian terhadap al-Quran yang dilakukan Wansbrough dengan menggunakan analisis sastera tidak masuk akal karena ada banyak kejanggalan. Kata-kata kunci: analisis sastera, Yahudi-Kristen, pengaruh, sejarah, Bibel.